PENGARUH LIKUIDITAS TERHADAP KINERJA KEUANGAN PADA PERUSAHAAN FARMASI YANG TERDAFTAR Di BURSA EFEK INDONESIA (BEI) PERIODE 2019-2023 - Putri, Ega Novita Setianing; Nawangsari, Ajeng Tita (Jurnal Riset Ilmu Akuntansi, 2026)
This study investigates the role of liquidity in shaping the financial performance of pharmaceutical companies listed on the Indonesia Stock Exchange (IDX) over the years 2019–2023. Liquidity is examined through the Current Ratio (CR), while financial performance is reflected by indicators such as Return on Assets (ROA) and Return on Equity (ROE). The research focuses on five pharmaceutical firms—PT Kimia Farma Tbk (KAEF), PT Indofarma Tbk (INAF), PT Kalbe Farma Tbk (KLBF), PT Darya- Varia Laboratoria Tbk (DVLA), and PT Tempo Scan Pacific Tbk (TSPC). The study adopts a quantitative framework supported by descriptive and comparative analysis, using secondary data sourced from the companies’ annual financial statements. The findings reveal notable disparities in both liquidity and profitability among the firms. KLBF consistently achieves the highest level of liquidity (CR 3.77–4.91) and demonstrates strong financial performance (ROA 10.15–12.59% and ROE 11.88–15.39%).  DVLA and TSPC maintain moderate liquidity positions (CR 2.18–3.00) with steady profitability (ROA 7.4–12.1% and ROE 10.6–17.0%). In contrast, KAEF and INAF report lower and more volatile CR values (1.03–2.06), along with weak and in some years negative profitability. Overall, the study concludes that variations in liquidity across pharmaceutical companies correspond to differences in their financial performance levels. Firms with higher CR generally achieve better ROA and ROE outcomes, suggesting that effective liquidity management can play a significant role in strengthening profitability.